1985
DOI: 10.1093/nar/13.20.7457
|View full text |Cite
|
Sign up to set email alerts
|

A novel expression selection approach allows precise mapping of the hepatitis B virus enhancer

Abstract: We have used a novel approach called expression selection to precisely define the hepatitis B virus (HBV) enhancer. Expression selection is based on a shuttle vector containing an enhancerless SV40 T antigen gene, the SV40 origin of replication and a plasmid replicon. This vector is linearized, ligated with the sonicated DNA to be analyzed and transfected into eukaryotic cells, where only plasmids which have incorporated an enhancer can express T antigen and therefore replicate. Vectors amplified by replicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 63 publications
1
69
0
Order By: Relevance
“…The insert was excised from the resulting construction by a SacI/HincII digestion and, after separation on an agarose gel, recovered by electroelution. The insert was then partially digested by AluI and the fragment containing the IRS-like and (interferon gene regulatory element) IRE-like sequences was purified as before and subcloned in pSVXB-pl [29] restricted by Sac1 and SmaI. The resulting construct, p56K-T, contains the -244 to -62 region of the IFI-56K promoter in front of the TATA box of the simian virus 40 (SV40) large Tantigen transcription unit.…”
Section: Dna Microinjection and Indirect Immunojluorescencementioning
confidence: 99%
See 2 more Smart Citations
“…The insert was excised from the resulting construction by a SacI/HincII digestion and, after separation on an agarose gel, recovered by electroelution. The insert was then partially digested by AluI and the fragment containing the IRS-like and (interferon gene regulatory element) IRE-like sequences was purified as before and subcloned in pSVXB-pl [29] restricted by Sac1 and SmaI. The resulting construct, p56K-T, contains the -244 to -62 region of the IFI-56K promoter in front of the TATA box of the simian virus 40 (SV40) large Tantigen transcription unit.…”
Section: Dna Microinjection and Indirect Immunojluorescencementioning
confidence: 99%
“…CsC1-double-purified supercoiled plasmid was microinjected in either HeLa or Vero nuclei as described [30]. 30 h after microinjection, the cells were fixed and stained as described [29].…”
Section: Dna Microinjection and Indirect Immunojluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…In 1985, for instance, enhancer regions were reported for the 3200 bp DNA of hepatitis B virus (Shaul et al, 1985 ;Tognoni et al, 1985), and, at the other end of the spectrum of genome sizes, for the major immediate-early gene of human cytomegalovirus (Boshart et al, 1985). The mechanisms of enhancer action remain somewhat mysterious.…”
Section: Aspects Of Virus Gene Expressionmentioning
confidence: 99%
“…Characterization of the celltype specificity of the HBV enhancers and promoters has suggested that the enhancer elements and the core and large surface antigen promoters may direct preferential gene expression in hepatoma cell lines Karpen et al, 1988;Antonucci & Rutter, 1989;Honigwachs et al, 1989;Yee, 1989;Raney et al, 1990;Chang et al, 1989;Patel et al, 1989;Shaul & Ben Levy, 1987;Yuh & Ting, 1993;Shaul et al, 1985; Publication number 8537-MEM from The Scripps Research Institute. Tognoni et al, 1985), whereas the major surface antigen gene appears to be expressed efficiently in a range of tissue culture cell types (Pourcel et al, 1982;De-Medina et al, 1988).…”
Section: Introductionmentioning
confidence: 99%